Double-bundle PCL Reconstruction: A Prospective Study of Two-year Patient Reported Outcomes with Stress Radiographs - Geeslin, Andrew (Orthop J Sports Med, 2017)
OBJECTIVES: Reconstruction of grade-III posterior cruciate ligament (PCL) ruptures has historically been compromised by graft elongation and residual laxity. The purpose of this study was to report prospectively collected two-year outcomes and failure rates of double-bundle PCL reconstruction in a consecutive patient series with patient reported outcomes and quantitative stress radiographs. It was hypothesized that double bundle PCL reconstruction would result in improved subjective clinical outcomes, restoration of knee stability, and result in high patient satisfaction. METHODS: A single surgeon consecutive series of patients that underwent double-bundle PCL reconstruction between June, 2010, and April, 2014, were followed prospectively. The technique is anatomically and biomechanically validated and utilizes two allografts (Achilles tendon for anterolateral bundle, tibialis anterior tendon for posteromedial bundle) in divergent femoral tunnels and a single tibial tunnel, each secured at the tibia at different knee angles to recreate the function of the two PCL bundles. Patient reported outcomes were collected preoperatively, and at a minimum two-year follow-up, including SF12, WOMAC, Tegner, Lysholm, and patient satisfaction. Posterior kneeling stress radiographs were obtained preoperatively and at the 6-month follow-up period. Failures were defined objectively as a difference of more than 3 mm in stress radiographs. RESULTS: Sixty patients had greater than 2 year follow-up (mean 2.9 yrs). All subjective outcome measures improved except SF-12 mental component which was unchanged. The mean Lysholm score improved from 48 to 79. The mean WOMAC score improved from 39 to 11. The median SF-12 physical component score improved from 32 to 55. The median Tegner activity score improved from 2 to 5. The median patient satisfaction score was 8. Stress radiographs were available for 36 patients and improved from a preoperative side-to-side difference of 9.6 mm to 1.0 mm at 6 months follow-up. One failure occurred in a patient who had an 8 mm side-to-side difference at final follow-up and 18 mm pre-operatively. CONCLUSION: Double bundle PCL reconstruction results in improved patient reported outcomes and restoration of posterior knee stability. High patient satisfaction and low failure rates were found in this cohort of patients.